Preparation and cytotoxicity of cisplatin-containing liposomes - Carvalho Júnior,A.D. (2007)
We encapsulated cisplatin into stealth pH-sensitive liposomes and studied their stability, cytotoxicity and accumulation in a human small-cell lung carcinoma cell line (GLC4) and its resistant subline (GLC4/CDDP). Since reduced cellular drug accumulation has been shown to be the main mechanism responsible for resistance in the GLC4/CDDP subline, we evaluated the ability of this new delivery system to improve cellular uptake. The liposomes were composed of dioleoylphosphatidylethanolamine (DOPE), cholesteryl hemisuccinate (CHEMS), and distearoylphosphatidylethanolamine-polyethyleneglycol 2000 (DSPE-PEG2000) and were characterized by determining the encapsulation percentage as a function of lipid concentration. Among the different formulations, DOPE/CHEMS/DSPE-PEG liposomes (lipid concentration equal to 40 mM) encapsulated cisplatin more efficiently than other concentrations of liposomes (about 20.0%, mean diameter of 174 nm). These liposomes presented good stability in mouse plasma which was obtained using a 0.24-M EDTA solution (70% cisplatin was retained inside the liposomes after 30 min of incubation). Concerning cytotoxic effects, they are more effective (1.34-fold) than free cisplatin for growth inhibition of the human lung cancer cell line A549. The study of cytotoxicity to GLC4 and GLC4/CDDP cell lines showed similar IC50 values (approximately 1.4 µM), i.e., cisplatin-resistant cells were sensitive to this cisplatin formulation. Platinum accumulation in both sensitive and resistant cell lines followed the same pattern, i.e., approximately the same intracellular platinum concentration (4.0 x 10-17 mol/cell) yielded the same cytotoxic effect. These results indicate that long-circulating pH-sensitive liposomes, also termed as stealth pH-sensitive liposomes, may present a promising delivery system for cisplatin-based cancer treatment. This liposome system proved to be able to circumvent the cisplatin resistance, whereas it was not observed when using non-long-circulating liposomes composed of phosphatidylcholine, phosphatidylserine, and cholesterol.